HUBUNGAN UMUR IBU, PARITAS DAN PEKERJAAN DALAM PENGGUNAAN KB SUNTIK 3 BULAN DI PUSKESMAS TOTOREJO - Gusti Ayu Ketut Dianasari; Yulizar Yulizar; Wahyu Ernawati; Siti Aisyah (Jurnal Ilmu Kesehatan MAKIA, 2023)
Indonesia is a country that has a large population. Indonesia is the 4th country with the largest population, namely in 2022 there are 2,757,738 people (Central Bureau of Statistics, 2023). According to Riskesdas (2018) the proportion of contraceptive use in women aged 10-54 years is as follows: condoms (1.1%), fem), 3 month injection (42.4%), no family planning (27.1%). The purpose of this study was to determine the relationship between maternal age, parity, and work in use at the Totorejo Health Center. This type of research uses a research designcross sectional. The population in this study is all family planning acceptors in 2022 with a total of 4874 family planning acceptors. The sample in this study used the Slovin formula so that 98 family planning acceptors were obtained using a sampling techniquesystematic random sampling. Data were analyzed by testChi-Square. Univariate analysis found that 3-month injectable family planning acceptors totaled 59 respondents (60.2%), which was greater than acceptors who did not use 3-month injectable family planning, totaling 38 respondents (39.8%). The results of the bivariate analysis found that there was a significant relationship between maternal age where the value (P-Value = 0.001), there is a significant relationship between parities where the value (P-Value = 0.000), there is a significant relationship between jobs where (P-Value= 0.007) in the use of 3-month injectable birth control. The conclusion is that there is a relationship between mother's age, parity, and occupation with the use of 3-month injectable birth control. It is hoped that couples of childbearing age will choose contraception according to the needs of the mother.